Evaluation of NKX3.1 and C-MYC expression in canine prostatic cancer - Fonseca-Alves, Carlos Eduardo [UNESP] (2018)
NKX3.1/C-MYC cross-regulation has been reported in the normal human prostate, and loss of NKX3.1 and gain of C-MYC seem to be important events in prostate cancer development and progression. The dog can be an interesting model for human prostatic disease, and yet only one previous research study has shown deregulation of NKX3.1 and MYC in the canine prostate. To address the expression of NKX3.1 and C-MYC in different canine prostatic lesions, this study verified the gene and protein expression of NKX3.1 and C-MYC in normal canine prostatic tissues. We identified a 26 kDa band that corresponded to the NKX3.1 protein, while C-MYC showed a 50 kDa band on Western blotting analysis of all prostatic tissues. We observed that NKX3.1 protein and transcript were down-regulated in prostate cancer (PC) samples compared with non-neoplastic samples. We also observed that C-MYC protein was overexpressed in PC samples compared with normal (P =.001) and proliferative inflammatory atrophy (PIA) samples (P =.003). We found a positive correlation between NKX3.1 and C-MYC protein expression in normal and PIA samples. Interestingly, a negative correlation (NKX3.1 downregulation and MYC overexpression) was observed between NKX3.1 and MYC transcripts in PC. Thus, samples with higher C-MYC expression also exhibited higher NKX3.1 expression, which indicates the regulation of C-MYC by NKX3.1 protein. As in humans, these two genes and proteins were found to be related to canine prostate cancer. However, in contrast from what is observed in humans, in canine PC samples, the downregulation of NKX3.1 cannot be explained by DNA hypermethylation.